The Relationship between Canva-Based Iqra' Learning Activities and Students' Quranic Reading Ability - Rosyidah, Ida; Rachman, Hakim Arip (Jurnal al-Thullab, 2025)
The aim of this research is to examine the relationship between students' activities in use the Iqra' method based on Canva media in Reading and Writing the Al-Qur’an learning and their ability to read the Al- Qur'an (in class VII SMPN 52 Bandung City). The approaches used in this research was quantitative, involving Class VII students at SMPN 52 Bandung City, with a correlational type of research. The data collection tools are through observation, interviews, tests (oral and written), questionnaires, and correlation analysis calculations using Pearson product moment. The results of this research found that learning activities regarding the ability to read the Al- Qur'an in class VII students were both at a moderate to good level. Furthermore, the results of statistical calculation analysis found that the level of correlation between learning activities and the ability to read the Al-Qur'an was in the medium category. This shows that the higher level of student involvement in digital Iqra-based Reading and Writing the Al-Qur’an learning can be associated with better Al-Qur'an reading abilities. Therefore, it can be concluded that the integration of digital media such as Canva in Reading and Writing the Al-Qur’an learning, can support student involvement and contribute positively to Islamic religion education learning, which is supported by digital and interactive media.